Aufgaben
Wende auf die Aufgaben die zweite binomische Formel an.
Aufgabe 1:
(6x - 8y)
2
Aufgabe 2:
(7x - 1y)
2
Aufgabe 3:
(5x - 6y)
2
Aufgabe 4:
(1x - 4y)
2
Aufgabe 5:
(5x - 8y)
2
Aufgabe 6:
(1x - 10y)
2
Aufgabe 7:
(7x - 2y)
2
Aufgabe 8:
(10x - 5y)
2
Aufgabe 9:
(6x - 10y)
2
Aufgabe 10:
(10x - 8y)
2
Aufgabe 11:
(1x - 6y)
2
Aufgabe 12:
(6x - 4y)
2
Lösungen
Aufgabe 1:
(6x - 8y)
2 = 36x
2 - 96xy + 64y
2
a = 6x | a2 = (6x)2 = 36x2 |
a = 8y | a2 = (8y)2 = 64y2 |
ab = 6x · 8y = 48xy | 2ab = 2 · 48xy = 96xy |
Aufgabe 2:
(7x - 1y)
2 = 49x
2 - 14xy + 1y
2
a = 7x | a2 = (7x)2 = 49x2 |
a = 1y | a2 = (1y)2 = 1y2 |
ab = 7x · 1y = 7xy | 2ab = 2 · 7xy = 14xy |
Aufgabe 3:
(5x - 6y)
2 = 25x
2 - 60xy + 36y
2
a = 5x | a2 = (5x)2 = 25x2 |
a = 6y | a2 = (6y)2 = 36y2 |
ab = 5x · 6y = 30xy | 2ab = 2 · 30xy = 60xy |
Aufgabe 4:
(1x - 4y)
2 = 1x
2 - 8xy + 16y
2
a = 1x | a2 = (1x)2 = 1x2 |
a = 4y | a2 = (4y)2 = 16y2 |
ab = 1x · 4y = 4xy | 2ab = 2 · 4xy = 8xy |
Aufgabe 5:
(5x - 8y)
2 = 25x
2 - 80xy + 64y
2
a = 5x | a2 = (5x)2 = 25x2 |
a = 8y | a2 = (8y)2 = 64y2 |
ab = 5x · 8y = 40xy | 2ab = 2 · 40xy = 80xy |
Aufgabe 6:
(1x - 10y)
2 = 1x
2 - 20xy + 100y
2
a = 1x | a2 = (1x)2 = 1x2 |
a = 10y | a2 = (10y)2 = 100y2 |
ab = 1x · 10y = 10xy | 2ab = 2 · 10xy = 20xy |
Aufgabe 7:
(7x - 2y)
2 = 49x
2 - 28xy + 4y
2
a = 7x | a2 = (7x)2 = 49x2 |
a = 2y | a2 = (2y)2 = 4y2 |
ab = 7x · 2y = 14xy | 2ab = 2 · 14xy = 28xy |
Aufgabe 8:
(10x - 5y)
2 = 100x
2 - 100xy + 25y
2
a = 10x | a2 = (10x)2 = 100x2 |
a = 5y | a2 = (5y)2 = 25y2 |
ab = 10x · 5y = 50xy | 2ab = 2 · 50xy = 100xy |
Aufgabe 9:
(6x - 10y)
2 = 36x
2 - 120xy + 100y
2
a = 6x | a2 = (6x)2 = 36x2 |
a = 10y | a2 = (10y)2 = 100y2 |
ab = 6x · 10y = 60xy | 2ab = 2 · 60xy = 120xy |
Aufgabe 10:
(10x - 8y)
2 = 100x
2 - 160xy + 64y
2
a = 10x | a2 = (10x)2 = 100x2 |
a = 8y | a2 = (8y)2 = 64y2 |
ab = 10x · 8y = 80xy | 2ab = 2 · 80xy = 160xy |
Aufgabe 11:
(1x - 6y)
2 = 1x
2 - 12xy + 36y
2
a = 1x | a2 = (1x)2 = 1x2 |
a = 6y | a2 = (6y)2 = 36y2 |
ab = 1x · 6y = 6xy | 2ab = 2 · 6xy = 12xy |
Aufgabe 12:
(6x - 4y)
2 = 36x
2 - 48xy + 16y
2
a = 6x | a2 = (6x)2 = 36x2 |
a = 4y | a2 = (4y)2 = 16y2 |
ab = 6x · 4y = 24xy | 2ab = 2 · 24xy = 48xy |